Conference Review: Experiencing Experimental Archaeology, May 2020 - Katharina Singer (EXARC Journal)
The conference “Experiencing Experimental Archaeology / Experimentelle Archäologie Erleben” took place between May 9th - 10th 2020 at the Lauresham Laboratory for Experimental Archaeology, part of the UNESCO World Heritage Lorsch Abbey site, Germany. In previous years the event was held on site through lectures, information booths and presentations, providing the visitors with information about current projects. This year, due to COVID-19 restrictions, it had to be undertaken digitally, as museums and other institutions were temporarily closed to the public. Therefore, the Open-Day at the Lauresham Laboratory for Experimental Archaeology was transformed into an online conference. The shift to going digital gave more international participants the opportunity to present their projects and institutions and to partake in the live online discussion. EXARC hosted the event, facilitating video access of the lectures to academic and non-academic participants, who could ask questions via the platform. These were answered directly after each talk via audio channel.